Peran Pola Asuh Orang Tua pada Perkembangan Motorik Kasar Anak Usia Prasekolah - Nursanti; Muhammad Khidri Alwi; Nur Ilah Padhila; Idelriani (Window of Nursing Journal, 2025)
In the process of development, one of the important aspects for the gross motor development of children is body movement which is based on the movement of large muscles, therefore great attention is needed for the development of children's gross motor skills from parents as well as teachers, because children's motoric development is very important in life. children later, the role of parents is very necessary in controlling or monitoring the growth and development of children physically, cognitively or socially. In monitoring children must be regularly and continuously. This study aims to determine the relationship between parenting style and gross motor development of preschool-aged children in kindergarten. Islam Marga Kaya Makassar. This study uses a correlational descriptive research design with a cross sectional study approach. The sampling technique was carried out using a total sampling technique with a total sample of 30 respondents. Data collection using a questionnaire. Methods of data analysis using univariate and bivariate analysis through the Chi-Square statistical test at a significant level of α <0.05. 5 people (16.7%) and children with gross motor development according to as many as 22 children (73.3%) while children with inappropriate categories totaled 8 children (20.0%), statistical tests obtained p value = 0.016 <α value (0.05) . The conclusion in this study is that there is a relationship between parenting parents and children's gross motor development in kindergarten. Makassar Rich Marga Islam. From the results obtained, it is suggested that parents can apply proper parenting, as well as monitor the growth and development of their children from a physical, cognitive and social perspective.